Nitric oxide and reactive oxygen species regulate the accumulation of heat shock proteins in tomato leaves in response to heat shock and pathogen infection - Piterková, Jana; Luhová, Lenka; Mieslerová, Barbora; Lebeda, Aleš; Petřivalský, Marek (Plant science, 2013)
Heat shock proteins (HSP) are produced in response to various stress stimuli to prevent cell damage. We evaluated the involvement of nitric oxide (NO) and reactive oxygen species (ROS) in the accumulation of Hsp70 proteins in tomato leaves induced by abiotic and biotic stress stimuli. A model system of leaf discs was used with two tomato genotypes, Solanum lycopersicum cv. Amateur and Solanum chmielewskii, differing in their resistance to fungal pathogen Oidium neolycopersici. Leaf discs were exposed to stress factors as heat shock and pathogen infection alone or in a combination, and treated with substances modulating endogenous NO and ROS levels. Two proteins of Hsp70 family were detected in stressed tomato leaf discs: a heat-inducible 72 kDa protein and a constitutive 75 kDa protein. The pathogenesis and mechanical stress influenced Hsp75 accumulation, whereas heat stress induced mainly Hsp72 production. Treatment with NO donor and NO scavenger significantly modulated the level of Hsp70 in variable manner related to the genotype resistance. Hsp70 accumulation correlated with endogenous NO level in S. lycopersicum and ROS levels in S. chmielewskii. We conclude NO and ROS are involved in the regulation of Hsp70 production and accumulation under abiotic and biotic stresses in dependence on plant ability to trigger its defence mechanisms.
Keywords: reaktivní formy kyslíku; reakce na tepelný šok; proteiny tepelného šoku HSP70; oxid dusnatý; Ascomycota; Solanum; nemoci rostlin; Heat-Shock Response; HSP70 Heat-Shock Proteins; Reactive Oxygen Species; Nitric Oxide; Plant Diseases; Solanum lycopersicum